أنموذج شبكة عصبية صنعية لتقدير التّبخر اليومي في محطة سد الباسل - Ghatfan Abdalkareem Ammar; Sharif Badr Hayek; Mais Mayassah (Tishreen University, 2019)
أنموذج شبكة عصبية صنعية لتقدير التّبخر اليومي في محطة سد الباسل غطفان عبد الكريم عمار شريف بدر حايك ميس مياسة تُشكِّل عملية التّبخر إحدى المكونات الأساسيّة للدورة الهيدرولوجيّة، والتّقدير الدقيق للتّبخر له أهميّة كبيرة في إدارة أنظمة الموارد المائيّة ودراسات الموازنة المائيّة. يهدف هذا البحث إلى دراسة كفاءة استخدام الشّبكات العصبيّة الصنعيّة (Artificial Neural Networks) في تقدير التّبخر اليومي في محطة سد الباسل الواقعة في محافظة طرطوس باعتماد بيانات مناخيّة يوميّة. حيث بُني الأنموذج الرياضي باعتماد أربعة بارامترات جوية كمدخلات للشّبكة العصبيّة الصنعيّة، وهي درجة حرارة الهواء الوسطية، الرطوبة النسبيّة الوسطية، الإشعاع الشمسي، سرعة الرياح الوسطية، في حين استُخدمت قيم التّبخر اليومي المقيسة من حوض التّبخر الأمريكي صنف A كمخرجات مأمولة للشّبكة المقترحة لغرض التحقق من صحة أدائها. تمّ بناء شبكة عصبيّة صنعيّة متعددة الطبقات باستخدام خوارزميّة الانتشار العكسي للخطأ، وحُدِّد عدد الطبقات الخفية وعدد العصبونات ودوال التفعيل المستخدمة في كل طبقة منها. توّصلت الدراسة إلى أن الشّبكة العصبيّة الصنعيّة ANN ذات الهيكلية (4-28-1) قادرة على التنبّؤ بالتّبخر اليومي بدقة عالية في منطقة الدراسة حيث بلغت قيمة معامل الارتباط (0.844)، وقيمة جذر متوسط مربع الخطأ (1.15 mm/day) وذلك في مرحلة الاختبار. ممّا يبيّن فعالية تقانة الشّبكات العصبيّة الصنعيّة ذات الانتشار العكسي للخطأ في تقدير التّبخر اليومي. Evaporation process is one of the basic components of the hydrological cycle, and the exact estimation of evaporation has great importance in water resources systems management and water balance studies. This research aims to study the efficiency of using artificial neural networks (ANNs) in estimation of daily evaporation from AL-BASEL reservoir located in Tartous by using daily meteorological data. The mathematical model was built based on four meteorological parameters as the network inputs (i.e. the mean air temperature, mean  relative humidity, solar radiation, mean wind speed), and the data of daily evaporation, which measured from the American pan class A used as the network output for checking its performance accuracy. A multilayer artificial neural network has been built by using error Back-propagation algorithm, and the number of hidden layers was selected and the number of neurons and activation functions which used in each layer of them. The study found that the artificial neural network ANN  of structure (4-28-1) able to predict the daily evaporation with high accuracy in the study area as the value of the correlation coefficient is (0.844), and the value of the root mean square error  is (1.15 mm/day) of testing data set. This clearly indicates the possibility of using ANN technique of error back-propagation for estimating the daily evaporation.